2021
DOI: 10.7554/elife.67999
|View full text |Cite
|
Sign up to set email alerts
|

Pak1 and PP2A antagonize aPKC function to support cortical tension induced by the Crumbs-Yurt complex

Abstract: The Drosophila polarity protein Crumbs is essential for the establishment and growth of the apical domain in epithelial cells. The protein Yurt limits the ability of Crumbs to promote apical membrane growth, thereby defining proper apical/lateral membrane ratio that is crucial for forming and maintaining complex epithelial structures such as tubes or acini. Here, we show that Yurt also increases Myosin-dependent cortical tension downstream of Crumbs. Yurt overexpression thus induces apical constriction in epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 88 publications
4
12
0
Order By: Relevance
“… 45 Alternatively, aPKC may target other actomyosin regulators or function through other apical polarity proteins implicated in the regulation of apical actomyosin contractility, such as Crumbs and Lulu2/Yurt. 24 , 41 , 45 , 46 , 47 , 48 In line with recent work showing aPKC prevents apical constriction by repressing apical Yurt accumulation, 36 we observed Yurt apical enrichment after optogenetic inactivation of aPKC .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“… 45 Alternatively, aPKC may target other actomyosin regulators or function through other apical polarity proteins implicated in the regulation of apical actomyosin contractility, such as Crumbs and Lulu2/Yurt. 24 , 41 , 45 , 46 , 47 , 48 In line with recent work showing aPKC prevents apical constriction by repressing apical Yurt accumulation, 36 we observed Yurt apical enrichment after optogenetic inactivation of aPKC .…”
Section: Discussionsupporting
confidence: 92%
“…Recent work showed that aPKC prevents Yurt mislocalization to the apical membrane of follicle cells, where Yurt binding to Crumbs induces apical constriction. 36 We therefore tested Yurt and Crumbs response in tissues clonally expressing UAS-LARIAT and exposed to light for 40 min. Crumbs largely maintained its apical localization, despite partial co-localization with the GFP::aPKC clusters ( Figures S2 C and S2D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations